Impact of MOOC-based professional development courses on self-directed and critical learning - Ardavani, Shahrzad (Proceedings of the International Conference on Networked Learning, 2018)
Recent research has revealed an increase in opportunities for MOOCs to provide students from different countries with an effective platform for learning. The main argument is that MOOCs can provide fast and easy access to western universities and their resources, and with that improve collaboration and interaction between nations. However, MOOCs have been criticized for being too challenging, specialized in certain teaching methods and not always meeting the expectations of the learners. Expectations are rooted in the way participants from different countries access and construct knowledge, and their individual way of learning may not be accounted for by the educational platform. This paper investigates professional learning within the context of a MOOC to improve learning experiences. The study starts from the assumption that learners with different cultural and educational backgrounds bring different expectations and assumptions to online learning. The research explores the extent to which participants’ expectations, learning goals and aims have been met through examination of their criticisms, critiques and concerns of a MOOC. Brookfield’s Critical Incident Questionnaire (CIQ) was used on a weekly basis to capture the experiences of six English language teachers undertaking a continuing professional development (CPD) MOOC over the span of four weeks (Brookfield, 1995). Three ‘Cs’, concern, critique and criticism, were used to explore learners’ responses. In this study a concern is something related to an activity or content that causes learners to worry; critique is defined as the act of expressing an opinion about the good and bad parts of a thing, and criticism is defined as the act of expressing disapproval and noting the faults of a thing. Findings illustrate the change in participants’ expectations and show them becoming aligned with the objectives of the course, critiquing rather than criticizing. This suggests that they started to take responsibility for their own learning and they became more reflective and analytical in their learning style. A wide range of critiques and criticisms that surfaced during the study have been identified around the content of the MOOC, particularly that the knowledge provided was too basic, and did not target experienced learners. Furthermore, the course lacked sufficient differentiation to meet participants’ metalanguage needs, and thus it did not account for terminology difficulties one would expect from participants with different professional backgrounds.